Targeting tumour-associated macrophages with CCR2 inhibition in combination with FOLFIRINOX in patients with borderline resectable and locally advanced pancreatic cancer: a single-centre, open-label, dose-finding, non-randomised, phase 1b trial. Issue 5 (May 2016) - Nywening, Timothy M; Wang-Gillam, Andrea; Sanford, Dominic E; Belt, Brian A; Panni, Roheena Z; Cusworth, Brian M; Toriola, Adetunji T; Nieman, Rebecca K; Worley, Lori A; Yano, Motoyo; Fowler, Kathryn J; Lockhart, A Craig; et al.
Summary: Background: In pancreatic ductal adenocarcinoma, the CCL2–CCR2 chemokine axis is used to recruit tumour-associated macrophages for construction of an immunosuppressive tumour microenvironment. This pathway has prognostic implications in pancreatic cancer, and blockade of CCR2 restores anti-tumour immunity in preclinical models. We aimed to establish the safety, tolerability, and recommended phase 2 oral dose of the CCR2 inhibitor PF-04136309 in combination with FOLFIRINOX chemotherapy (oxaliplatin and irinotecan plus leucovorin and fluorouracil). Methods: We did this open-label, dose-finding, non-randomised, phase 1b study at one centre in the USA. We enrolled treatment-naive patients aged 18 years or older with borderline resectable or locally advanced biopsy-proven pancreatic ductal adenocarcinoma, an Eastern Cooperative Oncology Group performance status of 1 or less, measurable disease as defined by Response Evaluation Criteria in Solid Tumors version 1.1, and normal end-organ function. Patients were allocated to receive either FOLFIRINOX alone (oxaliplatin 85 mg/m 2, irinotecan 180 mg/m 2, leucovorin 400 mg/m 2, and bolus fluorouracil 400 mg/m 2, followed by 2400 mg/m 2 46-h continuous infusion), administered every 2 weeks for a total of six treatment cycles, or in combination with oral PF-04136309, administered at a starting dose of 500 mg twice daily in a standard 3 + 3 dose de-escalation design. Both FOLFIRINOX and PF-04136309 were simultaneously initiated with a total treatment duration of 12 weeks. The primary endpoints were the safety, tolerability, and recommended phase 2 dose of PF-04136309 plus FOLFIRINOX, with an expansion phase planned at the recommended dose. We analysed the primary outcome by intention to treat. This trial is registered withClinicalTrials.gov, numberNCT01413022 . Results: Between April 19, 2012, and Nov 12, 2014, we treated 47 patients with FOLFIRINOX alone (n=8) or with FOLFIRINOX plus PF-04136309 (n=39). One patient had a dose-limiting toxic effect in the dose de-escalation group receiving FOLFIRINOX plus PF-04136309 at 500 mg twice daily (n=6); this dose was established as the recommended phase 2 dose. We pooled patients in the expansion-phase group (n=33) with those in the dose de-escalation group that received PF-04136309 at the recommended phase 2 dose for assessment of treatment-related toxicity. Six (75%) of the eight patients receiving FOLFIRINOX alone were assessed for treatment toxicity, after exclusion of two (25%) patients due to insurance coverage issues. The median duration of follow-up for treatment toxicity was 72·0 days (IQR 49·5–89·0) in the FOLFIRINOX alone group and 77·0 days (70·0–90·5) in the FOLFIRINOX plus PF-04136309 group. No treatment-related deaths occurred. Two (5%) patients in the FOLFIRINOX plus PF-04136309 group stopped treatment earlier than planned due to treatment-related toxic effects. Grade 3 or higher adverse events reported in at least 10% of the patients receiving PF-04136309 included neutropenia (n=27), febrile neutropenia (n=7), lymphopenia (n=4), diarrhoea (n=6), and hypokalaemia (n=7). Grade 3 or higher adverse events reported in at least 10% of patients receiving FOLFIRINOX alone were neutropenia (n=6), febrile neutropenia (n=1), anaemia (n=2), lymphopenia (n=1), diarrhoea (n=2), hypoalbuminaemia (n=1), and hypokalaemia (n=3). Therapy was terminated because of treatment-related toxicity in one (17%) of the six patients receiving FOLFIRINOX alone. 16 (49%) of 33 patients receiving FOLFIRINOX plus PF-04136309 who had undergone repeat imaging achieved an objective tumour response, with local tumour control achieved in 32 (97%) patients. In the FOLFIRINOX alone group, none of the five patients with repeat imaging achieved an objective response, although four (80%) of those patients achieved stable disease. Interpretation: CCR2-targeted therapy with PF-04136309 in combination with FOLFIRINOX is safe and tolerable. Funding: Washington University–Pfizer Biomedical Collaborative.